Lancet dynamics in greater horseshoe bats, Rhinolophus ferrumequinum. - Weikai He; Scott C Pedersen; Anupam K Gupta; James A Simmons; Rolf Müller (PLoS ONE, 2015)
Echolocating greater horseshoe bats (Rhinolophus ferrumequinum) emit their biosonar pulses nasally, through nostrils surrounded by fleshy appendages ('noseleaves') that diffract the outgoing ultrasonic waves. Movements of one noseleaf part, the lancet, were measured in live bats using two synchronized high speed video cameras with 3D stereo reconstruction, and synchronized with pulse emissions recorded by an ultrasonic microphone. During individual broadcasts, the lancet briefly flicks forward (flexion) and is then restored to its original position. This forward motion lasts tens of milliseconds and increases the curvature of the affected noseleaf surfaces. Approximately 90% of the maximum displacements occurred within the duration of individual pulses, with 70% occurring towards the end. Similar lancet motions were not observed between individual pulses in a sequence of broadcasts. Velocities of the lancet motion were too small to induce Doppler shifts of a biologically-meaningful magnitude, but the maximum displacements were significant in comparison with the overall size of the lancet and the ultrasonic wavelengths. Three finite element models were made from micro-CT scans of the noseleaf post mortem to investigate the acoustic effects of lancet displacement. The broadcast beam shapes were found to be altered substantially by the observed small lancet movements. These findings demonstrate that-in addition to the previously described motions of the anterior leaf and the pinna-horseshoe bat biosonar has a third degree of freedom for fast changes that can happen on the time scale of the emitted pulses or the returning echoes and could provide a dynamic mechanism for the encoding of sensory information.